Bandage Contact Lens Application Reduces Fibrotic Wound Healing of Flap Margins after FS-LASIK: A Prospective Randomized Clinical Trial - Li-Quan Zhao; Liang-Mao Li; Jun Liu; Peng Li (Journal of Ophthalmology)
Purpose. To assess the efficacy of applying bandage contact lens (BCL) in reducing the fibrotic healing response of flap margins following femtosecond laser in situ keratomileusis (FS-LASIK). Methods. In this prospective, randomized, interventional, observer-masked trial, 41 patients (82 eyes) with myopia and/or myopic astigmatism were scheduled to undergo FS-LASIK. After surgery, patients were fitted with a BCL in one eye (BCL eyes, n=41) but not in the contralateral eye (control eyes, n=41), following randomized allocation of the BCL to the left or right eye of each patient. The BCL was left in place overnight and removed the following morning. All eyes subsequently received standardized postoperative treatments. Patients were followed up for 6 months. We evaluated patients’ self-reported postoperative symptom scores for pain, photophobia, tearing, and foreign-body sensation. At 6 months after surgery, we examined the corneal flap margin and adjacent regions, and photographed them using slit-lamp biomicroscopy, to subjectively evaluate the wound healing response. Results. Postoperative pain and photophobia were milder in the BCL group than in the control group (P=0.041 and P=0.003, respectively), but patients felt more foreign-body sensation in the eye with a BCL than in the control eye (P=0.001). There was no significant difference in tearing score between BCL eyes and control eyes (P=0.118). Regarding the fibrotic healing response of the flap margin, control eyes showed a wide, bright peripheral circumferential band with a spiculated edge and high reflectivity; conversely, BCL eyes showed a markedly narrower and smoother peripheral circumferential band, with a less spiculated edge and lower reflectivity (P<0.001). Conclusion. Patients felt less discomfort in eyes treated with a BCL after FS-LASIK than in control eyes. BCL-treated eyes also had a less intense wound healing response at the flap margins than control eyes in some of patients. BCLs may merit consideration as a treatment option after FS-LASIK for special patients. This trial is registered with ChiCTR1800016579.